Edukasi pemberian makanan tambahan pada balita sebagai upaya pencegahan stunting di UPTD PUSKESMAS Martimbang Pematangsiantar [Education on providing supplementary food to toddlers as an effort to prevent stunting at the Martimbang Pematangsiantar Community Health Center] - Damanik, Derma Wani; Saragih, Julwansa; Yunia, Eva Anita; Dewi, Rani Sartika (Indonesia Berdaya, 2025)
Abstract. Stunting is a disorder of growth and development in children due to chronic malnutrition and repeated infections, which is characterized by their length or height being below the established standard. The toddler group needs attention because they are a group that is vulnerable to malnutrition. Malnutrition is still a major problem in infants and children under five years of age (toddlers) globally. In 2025, the world of nutrition is expected to face a number of new complex issues. Not only challenges in terms of nutritional problems, such as multiple malnutrition, obesity, and stunting, but also changes in education models and nutritional intervention approaches. The incidence of stunting in North Sumatra Province in 2023 reached 19,298 people with details of toddlers with stunting as many as 18.9%, malnutrition 7.9%, undernutrition 13.2% and overnutrition 3.5%. The incidence of stunting in Pematang Siantar City was 303 people, with the number of toddlers with stunting as many as 7.7%, malnutrition 4.2%, undernutrition 7.2% and overnutrition 4.2%. The implementation of community service carried out in the form of providing education on providing additional food for toddlers. The target of this activity was mothers with toddlers in the working area of the UPTD Martimbang Pematangsiantar Health Center as many as 12 people. The results of community service obtained that before education, the majority of the knowledge of the education participants was sufficient as many as 7 people (58.3%) and after receiving education, the majority of knowledge became good as many as 10 people (83.3%). Community service activities received a good and positive response from the participants and there was an increase in the knowledge of mothers who have children and children will be healthy according to their growth and development. Abstrak. Stunting merupakan gangguan pertumbuhan dan perkembangan anak akibat kekurangan gizi kronis dan infeksi berulang, yang ditandai dengan panjang atau tinggi badannya berada dibawah standar yang ditetapkan. Kelompok balita perlu mendapat perhatian karena merupakan kelompok yang rawan terhadap kekurangan gizi. Malnutrisi masih menjadi permasalahan utama pada bayi dan anak di bawah lima tahun (balita) secara global. Pada tahun 2025, dunia gizi diperkirakan akan menghadapi sejumlah isu baru yang kompleks. Tidak hanya tantangan dari sisi masalah gizi, seperti malnutrisi ganda, obesitas, dan stunting, tetapi juga perubahan dalam model pendidikan dan pendekatan intervensi gizi.  Angka kejadian stunting di Provinsi Sumatera Utara tahun 2023 mencapai 19.298 orang dengan rincian balita dengan stunting sebanyak 18,9%, gizi buruk 7,9%, gizi kurang 13,2% dan gizi lebih 3,5%. Angka kejadian stunting di Kota Pematang Siantar sebanyak 303 orang, dengan jumlah balita stunting sebanyak 7,7%, gizi buruk 4,2%, gizi kurang 7,2% dan gizi lebih 4,2%. Pelaksanaan pengabdian masyarakat yang dilakukan berupa pemberian edukasi pemberian makanan tambahan pada balita. Sasaran pada kegiatan ini adalah ibu dengan balita di wilayah kerja UPTD Puskesmas Martimbang Pematangsiantar sebanyak 12 orang. Hasil pengabdian masyarakat diperoleh bahwa sebelum edukasi mayoritas pengetahuan peserta edukasi adalah cukup sebanyak 7 orang (58,3%) dan setelah memperoleh edukasi mayoritas pengetahuan menjadi baik sebanyak 10 orang (83,3%). Kegiatan pengabdian masyarakat memperoleh respon yang baik dan positif dari peserta kegiatan dan terjadinya peningkatan pengetahuan  ibu yang memiliki anak serta anak akan menjadi sehat sesuai dengan pertumbuhan dan perkembangannya.